E-HRM: A Paradigm Shift in HR Practices and its Effects on Perception of Employees Towards Accepting this New Technology - Yadav, Deepesh Kumar; Yadav, Jaya; Malik, Rajeev (Prabandhan: Indian Journal of Management, 2019)
Since 1990, the perspective of administration towards its representatives started changing, part and commitment of human resource (HR) as an ability to pool additional outcome from an individual became vital to the point that a large number of industries began to center their vision and mission around the general population who work for them. The part and obligations of human asset administration changed because of progress in government arrangements, associations, work enactments, and innovation. Organizations put up a noteworthy attention on human capital instead of money related capital. Organizations predicted that business needs workforce that can give a firm a decisive competitive advantage over other organizations. This paper attempted to identify the effect of e-HRM practices as a shift in paradigm of HR practices, its effect on functional and interpersonal variables in employees' perception in information technology enabled services companies, that is, ITES companies of Ghaziabad.